Effects of calcium chloride coadministered with neostigmine on neuromuscular blockade recovery: A double-blind randomised study. Issue 9 (September 2017) - Ju, Jae-Woo; Kim, Hyun-Chang; Yoon, Sehee; Hong, Deok Man; Park, Hee-Pyoung
Abstract : BACKGROUND: Ionised calcium plays an important role in neuromuscular transmission, but its effects on the reversal of nondepolarising neuromuscular blockade have not been fully evaluated. OBJECTIVE: We examined whether calcium chloride coadministered with neostigmine could enhance the rate of neuromuscular recovery. DESIGN: Randomised double-blind trial. SETTING: A tertiary teaching hospital. PATIENTS: In total, 53 patients undergoing elective surgery under general anaesthesia with neuromuscular monitoring by acceleromyography using a TOF-Watch SX monitor. INTERVENTIONS: Patients were randomly allocated to receive either 5 mg kg −1 of calcium chloride (calcium group, n = 26) or the same volume of normal saline (control group, n = 27) coadministered with 25 μg kg −1 of neostigmine and 15 μg kg −1 of atropine at the end of surgery. MAIN OUTCOME MEASURES: The primary end point was the neuromuscular recovery time [time from neostigmine administration to recovery of the TOF ratio (TOFr) to 0.9]. Secondary end points included the TOFr at 5, 10 and 20 min after neostigmine administration and the incidence of postoperative residual curarisation (PORC), defined as a TOFr less than 0.9 at each time point. RESULTS: The neuromuscular recovery time was significantly faster in the calcium group than in the control group (median [Q1 to Q3 ]; 5.0 [3.0 to 7.0] vs. 6.7 [5.7 to 10.0] min, respectively; P = 0.007). At 5 min after neostigmine administration, the TOFr was higher [87 (74 to 100) vs. 68 (51 to 81)%, respectively; P = 0.002] and the incidence of PORC was lower (50.0 vs. 81.5%, respectively; P = 0.016) in the calcium group than in the control group. There were no differences between the two groups with respect to the TOFr or incidence of PORC at 10 and 20 min after neostigmine administration. CONCLUSION: Calcium chloride coadministered with neostigmine enhanced neuromuscular recovery in the early period of nondepolarising neuromuscular blockade reversal.